“Angkatan Korona”: Stigma Terhadap Lulusan SMA Angkatan 2020 - Ratmanda Ratmanda (Universitas Muslim Maros, 2022)
The pandemic Covid-19, which has spread throughout the world including Indonesia, has had a major impact on various aspects of life, including in the field of education. While the existing literatures are more related to stigma on people infected with Covid-19 and on the health workers who care for them, this article is deals with stigma against 2020 high school graduates and those who enrolled college in the same year, and they are labeled